2005
DOI: 10.1212/01.wnl.0000188898.02018.95
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, delivery, and birth outcome in women with multiple sclerosis

Abstract: Using data from the compulsory Medical Birth Registry of Norway, the authors investigated the effect of maternal multiple sclerosis (MS) on pregnancy, delivery, and birth outcome in 649 births by MS mothers and 2.1 million control births. The mothers with MS had a higher proportion of neonates small for gestational age and also more frequent induction and operative interventions during delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
4
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 11 publications
11
136
4
9
Order By: Relevance
“…While some studies have shown a higher rate of assisted vaginal deliveries, for example requiring induction and slower progression of labor, 5 there is evidence to suggest that mothers and newborns do equally well and do not have longer birth hospitalizations that non-MS counterparts, even when accounting for longer disease duration and increased disability. 15 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have shown a higher rate of assisted vaginal deliveries, for example requiring induction and slower progression of labor, 5 there is evidence to suggest that mothers and newborns do equally well and do not have longer birth hospitalizations that non-MS counterparts, even when accounting for longer disease duration and increased disability. 15 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,12 Use of DMTs then necessitates education about consistent contraception and safety while breastfeeding. For example, while there is no evidence that glatiramer acetate is absorbed into a newborn's gastrointestinal tract to any significant degree, safety has not been established.…”
mentioning
confidence: 99%
“…En norsk studie viste at barn av mødre med multippel sklerose gjennomsnittlig hadde drøyt 100 g lavere fødselsvekt enn andre barn, og at kvinnen oftere blir forløst med keisersnitt (31).…”
Section: Fødselunclassified
“…Badanie PRIMS (Pregnancy-Related Relapse in Multiple Sclerosis) wykazało, że SM nie ma bezpośredniego wpływu na częstość poronień, ciąż pozamacicznych czy na występowanie wad wrodzonych u płodu [27,28]. Inne badania również nie potwierdziły negatywnego wpływu SM na płodność ani śmiertelność okołoporodową [29][30][31]. Ogólnie, czę-stość rzutów SM zmniejsza się w trakcie ciąży.…”
Section: Aspekty Związane Z Ciążą Menopauzą I Terapią Hormonalnąunclassified